The Problems of Online Learning for Islamic Education Subjects During the Covid-19 Pandemic in Vocational High Schools: Problematika Pembelajaran Daring Mata Pelajaran PAI Dimasa Pandemi Covid-19 Di Sekolah Menengah Kejuruan - Siswati Siswati; Istikomah Istikomah (Universitas Muhammadiyah Sidoarjo, 2022)
This article aims to find out the problems of online learning of Islamic religious education subjects during the covid-19 pandemic, there are several research results, namely: (1) In the online learning process of PAI folders during the covid pandemic, it has been going well, by providing online material and giving assignments. utilizing the WhatsApp Group application, (2) The problems that arise during online learning from students are; lack of interest in learning, limitations of devices and networks, low understanding, lack of mastery of the atmosphere in the classroom and mastery of the field of technology (3) Efforts made by the school are to facilitate students who are constrained by networks and devices as well as school teachers and conduct coaching and include teachers, especially Islamic religious education teachers.